ANALISIS TANTANGAN GURU DALAM MENGGUNAKAN TEKNOLOGIGADGET(HP)PADAPROSESPEMBELAJARANDISDN1TAROGONG - Nuri Sakinah; Fitri Ayu Febrianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In the rapidly developing digital era, the use of technology such as mobile phoneshas become an inseparable part of the learning process at various levels ofeducation. The presence of this technology offers many opportunities to improvethe quality of learning, such as facilitating access to information, supportinginteractive learning, and helping students understand material in a more engagingand contextual way. However, the implementation of technology in education alsopresents various challenges that must be faced by teachers.One of the main obstacles is the limited technological skills possessed by someteachers, especially those who are not yet familiar with using digital devices inteaching activities. In addition, there is still an infrastructure gap, such as limitedinternet access and supporting devices in certain areas, which hinders the optimaluseoftechnology.Moreover,excessiveuseofmobilephonescanleadtonegativeimpacts, such as decreased learning concentration and increased studentdependence on gadgets.To overcome these challenges, appropriate and sustainable solutions are needed.Technology training for teachers is an important step so that they can utilizetechnology effectively in the classroom. Furthermore, improving access toinfrastructure must be a priority. On the other hand, teachers need toimplementbalancedandwisemanagementoftechnologyusesothatstudentsremainfocusedonlearningobjectives.Withastrategicapproach,technologyintegrationcancreatea more effective, engaging, and relevant learning experience that aligns with theneeds of the modern era.